Automatic Neutral-section Passing Control for HXD1C Electric Locomotive - WANG Yu; LI Peng; YAN Gang; JIANG Fan (机车电传动)
The characteristic and principles of HXD1C electric locomotive automatic neutral-section passing control were introduced.Strategy of real-time traction power reduction slope was given to resolve the unbalance of traction power adjustment below fixed power reduction slope after entering neutral-section. The calculation and advantage of real-time traction power reduction slope was especially introduced in detail. Application indicated that the reduction of traction power was accurately after strategy of real-time power reduction slope applied, which helped HXD1C locomotive passing the neutral-section safely with heavy haul train.